2017
DOI: 10.7759/cureus.1412
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional Responses to Standard Therapy in a Patient with Metastatic HER2-Positive Breast Cancer

Abstract: Patients with metastatic breast cancer involving the liver and brain often have short overall survival. Here, we report a case of de novo metastatic breast cancer with multiple liver metastases at initial diagnosis in February 2011 in a 35-year-old Caucasian female patient. The histology was poorly differentiated invasive ductal carcinoma (estrogen and progesterone receptor negative, HER2 positive) and the patient was negative for germline BRCA 1 and 2 mutations. Systemic therapy with trastuzumab and docetaxel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Therefore, refractory MBC generally harbors a more dismal prognosis than dnMBC (27,(32)(33)(34)(35)(36). Following active treatment, some patients with dnMBC can obtain a long survival time (37).…”
Section: Heterogeneity Of Dnmbcmentioning
confidence: 99%
“…Therefore, refractory MBC generally harbors a more dismal prognosis than dnMBC (27,(32)(33)(34)(35)(36). Following active treatment, some patients with dnMBC can obtain a long survival time (37).…”
Section: Heterogeneity Of Dnmbcmentioning
confidence: 99%
“…A clear delineation is described with improved quality of life measures despite the terminality of the primary cancer. Concurrently, 14 studies noted statistically significant survival rates in individuals who underwent palliative mastectomy [11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Of these aggregates, three studies noted no difference in patient survival outcome and concluded with conflicting data [25][26][27].…”
Section: Literature Reviewmentioning
confidence: 99%